Cross-country analysis of social entrepreneurship ecosystem and support system in India and Malaysia - Nurhanani, Izzati; Puteri Fadzline, Muhamad Tamyez; B., Sripirabaa; Kumar, Senthil (SCMS Group of Educational Institutions, 2023)
The social entrepreneurship ecosystem cannot thrive without strong support structures. This study examines the status of social entrepreneurship and the support available to social entrepreneurs in two developing economies, viz. Malaysia and India and suggests potential improvements. The interview technique was used to collect data from social entrepreneurs running leveraged non-profit enterprises, hybrid non-profit enterprises, and traditional NGOs. Interview data were analyzed through thematic analysis, and the following five overarching themes were identified in Malaysia: training, grants from companies, accreditation by SMSE, relationships among social entrepreneurs, and university students as potential social entrepreneurs. In India, the following six themes were identified: addressing social problems, building a community for support, training, funding and grants, incubation and acceleration, and education. In Malaysia, social entrepreneurs' role and innovation enhancement in this sector are the support structures with potential improvement possibilities. Whereas, in India, potential improvement is possible in incubation, acceleration and mentoring, access to funds, resources for enhancing entrepreneurial competence, human capital, and cultural challenges. Considering future opportunities, it is important to focus on potential improvements and channel the investment efforts toward real problems to achieve meaningful results. Once all the stakeholders understand the impact of such investments, the adoption will be much better. Hence, in the long run, it is imperative to define what constitutes a significant impact and develop systems to monitor and measure the progress.